Better Outcomes in Severe and Morbid Obese Patients (BMI>35 kg/m2) in Primary Endo-Model Rotating-Hinge Total Knee Arthroplasty. (30th April 2012) - Lozano, Luis M.; López, Vicente; Ríos, José; Popescu, Dragos; Torner, Pere; Castillo, Félix; Maculé, Francisco
Abstract : The Endo-Model rotating-hinge prosthesis is preferably indicated as a primary implant in patients with advanced axial deviation of the lower limbs or unstable knees with severe bone defects. Outcomes were studied in 111 knees, operated in a three-year period; the mean followup was 28 months. Joint balance enhancement and limbs mechanical axis correction were achieved after surgery. There were 6 deep infections and 16 patients referred postoperative anterior knee pain. WOMAC index scores disaggregated by gender and BMI showed better outcomes in obese patients (specifically, those with a BMI of 35–40 kg/m 2 ) and in men. Although the lack of a control group did not allow definite conclusions and despite a nonnegligible complication rate, our results reveal that the Endo-Model total knee arthroplasty can be a useful tool to deal with severe and morbid obese patients affected of severe gonarthrosis associated with marked axial deviations, ligament instability, or bone defects.